An assessment model of historical thinking skills by means of the RASCH model - Ofianto, Ofianto; Suhartono, Suhartono (Graduate School of Universitas Negeri Yogyakarta & Himpunan Evaluasi Pendidikan Indonesia (HEPI), 2015)
This study was conducted to produce a model and instruments of historical thinking skills in the history subject at the senior high school (SHS) and to identify SHS students' historical thinking skills. The study was conducted in two stages, namely model development and instrument development altogether with a small-scale tryout and a large-scale tryout. The test for each tryout consisted of six and five sub-test sets. Each test set contained 20 anchor items. The sample for each tryout comprised 1573 and 2613 testees. The data was analyzed by means of Partial Credit Model (PCM) using the QUEST program. The overall tryout results indicate that, based on the criteria for an INFIT MNSQ mean of 0.1 and a standard deviation of 1.0, the tests fit the PCM. The reliability coefficients of the tests for the tryouts are moderately good; the Cronbach's alpha coefficients are, respectively, 0.65 and 0.54. The lowest score of historical thinking skills is -.352 and the highest is +1.21 in an ideal range of -4.0 to +4.0. In overall, the testees' scores are not satisfactory. Only 5.89% of the testees are above the expected median.